Breast Implant Selection: Consensus Recommendations Using a Modified Delphi Method. Issue 5 (May 2019) - Magnusson, Mark R.; Connell, Tony; Miroshnik, Michael; Layt, Craig; Ashton, Mark; Deva, Anand K.; Farrow, Hamish; Januszkiewicz, Janek
Abstract : Background: Geographical differences in breast implant selection approaches exist, and clinical data to guide the process are limited. Developing knowledge of implant-related risk factors further complicates the process. This analysis aimed to establish expert consensus on considerations for breast implant selection in Australia and New Zealand based on practice patterns in those countries. Methods: A modified Delphi method was used to gain consensus from experts in breast augmentation surgery in Australia and New Zealand. Panelists anonymously completed an initial questionnaire on current considerations in implant selection, discussed a summary of their responses in a live meeting, and completed a final consensus survey based on their live recommendations. Results: Seven panelists completed the final consensus survey. Consensus recommendations included ensuring consideration of proper surgical technique (pocket formation, positioning of implant) and patient tissue and anatomical characteristics, weighing relative expected results of various surface textures, sizes, and degrees of cohesivity, and careful contemplation of the migration risk. Conclusions: This modified Delphi exercise provided consensus recommendations on the key factors involved in implant selection from the perspective of plastic surgeons with practices in Australia and New Zealand. A primary recommendation was that the choice of implant for each patient should be individualized to patient tissue and anatomical characteristics.